Values education in early childhood development for social transformation in South Africa - Kanya Padayachee (Perspectives in Education)
Three decades into democracy, the conspicuous prevalence of immoral and unethical behaviour in South African society is indisputable. In 1997, this society was alerted to “a moral timebomb” (RSA, MRM, 2000) and a 2019 review report (DPME, 2019) confirmed the erosion of its social fabric and morality. Over the years, various initiatives and programmes aimed at inspiring or restoring morals, values and ethics emerged. However, these patchy, disconnected attempts have failed to stem the tide of social deterioration. Research indicates that interventions for behaviour and attitude changes are most efficacious in the early childhood phase. Accordingly, a doctoral study (Padayachee, 2022) proposed an early childhood development integral education and Ubuntu approach to foster the values of social responsibility and citizenship in preschoolers. The study included, in the exploratory phase, the category of values education, which is the focus of this paper. Data were gathered through focus group interviews with early childhood development staff, parents and community members in six pre-schools and analysed thematically. The findings on this specific category are presented to validate the argument that the explicit inclusion of values in early childhood development has the potential to build progressively a foundation for a moral and ethical  society and possibly impact social transformation in South Africa.